Pemberdayaan Duta Pariwisata Sebagai Agen Promosi Destinasi Wisata Berbasis Kearifan Lokal di Kabupaten Asahan - Rahmad Kurnia Abdik Nasution; Sitti Nurlaeli; Femmy Indriany Dalimunthe (Jurnal Pengabdian Masyarakat, 2026)
This community service program aims to empower tourism ambassadors in Asahan Regency as agents for promoting tourism destinations based on local wisdom. The program responds to the limited capacity of tourism ambassadors in utilizing local cultural potential and digital media for promotion. The activity was conducted on August 21, 2024, through a participatory workshop approach involving lectures, discussions, hands-on practice, and digital campaign simulations. The results indicate a significant improvement in participants’ knowledge, skills, and confidence in developing creative promotional strategies. Participants were able to identify and transform local cultural potential into competitive tourism promotion content. This program contributes to sustainable tourism development by strengthening local identity and enhancing community-based tourism promotion. The implication highlights the importance of continuous capacity building for tourism stakeholders.